Brain functional network connectivity development in very preterm infants: The first six months. (July 2016) - He, Lili; Parikh, Nehal A.
Abstract: Nearly 10% of premature infants are born very preterm at 32 weeks gestational age or less in the United States. Up to 35% of these very preterm survivors are at risk for cognitive and behavioral deficits. Yet accurate diagnosis of such deficits cannot be made until early childhood. Resting-state fMRI provides noninvasive assessment of the brain's functional networks and is a promising tool for early prognostication. In our present study, we enrolled a cohort of very preterm infants soon after birth and performed resting state fMRI at 32, 39 and additionally at 52 weeks postmenstrual age. Using group probabilistic independent component analysis, we identified the following resting-state networks: visual, auditory, motor, somatosensory, cerebellum, brainstem, subcortical gray matter, default mode, executive control, and frontoparietal network. We observed increasing functional connectivity strength from 32 to 52 weeks postmenstrual age for the auditory, somatosensory, visual, subcortical gray matter, executive control, and frontoparietal networks. Future studies with neurodevelopmental follow-up are needed to potentially identify prognostic biomarkers of long-term cognitive and behavioral deficits. Highlights: Several important brain networks can be identified by 32 weeks postmenstrual age. There is increasing functional connectivity strength from 32 to 52 weeks postmenstrual age. We highlight the maturation of several networks over the first six months after preterm birth.